UNIT 28.8 GILA, a Replacement for the Soft‐Agar Assay that Permits High‐Throughput Drug and Genetic Screens for Cellular Transformation. Issue 1 (10th October 2016) - Izar, Benjamin; Rotem, Asaf
Abstract : For the last five decades, measuring the ability of cells to grow in soft agar has served as the gold standard assay for in vitro cellular transformation. Nevertheless, the soft agar colony formation assay is time consuming and ill‐suited for high‐throughput screens. This unit describes an equally qualitative and quantitative assay known as growth in low attachment or GILA. The GILA assay is suitable for high‐throughput pharmacological or genetic screens and allows the simultaneous examination of multiple cell lines and experimental perturbations. GILA conditions are specific and relevant to the transformed state because they depend on a property of cancer cells that is not shared by non‐transformed cells. The GILA assay enables ex vivo drug sensitivity testing of patient‐derived tumor cells to define precise treatments for individual patients. © 2016 by John Wiley & Sons, Inc.